Iraqi Women in Diasporic Spaces: Political Mobilization, Gender & Citizenship - Nadje Al-Ali (Revue des Mondes Musulmans et de la Méditerranée)
This article examines the political mobilization of Iraqi women activists in diasporic spaces, including the U.K. the U.S., Jordan as well as women’s activism inside Iraq. It addresses two main questions: 1) in how far the different political, economic and legal conditions in the UK, US and Jordan shape women’s activities or lack thereof, and 2) the relationships and dynamics between Iraqi women activists from the diaspora and inside Iraq. It is based on original empirical data obtained through fieldwork in the UK, US and Jordan in 2004 & 2005. Informal interviews and participant observation are the main methods for an ongoing wider project about Iraqi women’s contribution to political transition. The comparative dimension is particularly important since general political climate and culture, as well as historical migration trajectories, gender ideologies and relations vary in the three host countries. The author maps out the existing women’s organizations, groups and networks and discusses impediments and obstacles to a greater involvement in political processes. One important dimension is the complex relationship between women who remained inside Iraq and those who returned post-2003 or are active while being based outside.